Deep trouble - Thompson, Lesley (Oxford University Press, 2010)
Amy and Matt are bored. They don't want to study for their exams. They want to have a good time. So they drive to the marina at West Palm Beach, and Matt jumps onto one of the boats. 'We can go anywhere!' he jokes. But when the owners of the boat come back and find them, Amy and Matt are in deep trouble. Matt is a good swimmer and enjoys scuba-diving, but now he must dive for their lives.